PERAN DESIGN & CREATIVE MANAGER DAN CORPORATE RELATIONS & SPONSORSHIP MANAGER DALAM PROGRAM GOVERNMENT PUBLIC RELATIONS UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT KOTA SEMARANG DALAM MENGGUNAKAN LAPOR SEMAR SOLUSI AWP SEBAGAI KANAL PENGADUAN RESMI KOTA SEMARANG - Gabriella Audrey Ivanka Dermawan; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
Low public participation and knowledge in using Lapor Semar Solusi AWP as the official complaint channel of Semarang City are influenced by its rebranding from Sapa Mbak Ita. The main issues include low public awareness of the new service identity, low trust in report follow-ups, and minimal utilization despite high public reporting needs. This study aims to explain and evaluate the role of Government Public Relations in increasing public awareness, trust, and participation. The theoretical framework includes Government Public Relations, awareness, trust, and customer journey. An implementative approach was applied through an integrated communication campaign titled Cipta Seni Bahana Aspirasi #NgadudiLaporSemar, conducted via media relations, public education campaigns, event activations, and digital media. The results show increased public awareness, improved trust in the reporting system, and growth in new users, indicating stronger government–public relationships through participatory and educational two-way communication.